Epiphytic Orchid and Host Tree Inventory in Bulu Pattanunang Protected Forest - Maros South Sulawesi - Warseno, Tri; Arinasa, Ida Bagus Ketut (Proceeding International Conference on Global Resource Conservation, 2013)
Bulu Pattanunang protected forest is located in Maros, South Sulawesi Province. Inventory of epiphyte orchids was conducted to study orchid diversity in Bulu Pattanunang protected forest. Observation of orchid within host trees was also done to study the preference host trees for orchid growth. It was recorded that there were 27 orchid species belonging to 16 genera, totally 783 individuals recorded and 20 host trees species belonging to 19 genera. The most common epiphyte orchids were Dendrobium crumenatum Sw. (182 individual), followed by Aerides odorata Lour. (132 individual), Coelogyne multiflora Schltr. (81 individual) and Eria javanica (Sw.) Bl. (71 individual). Mangifera indica and Arenga pinnata were the most preference host tree for epiphytic orchid. Association relationship between epiphytic orchids and its host are discussed in this paper. Â Keywords: epiphytic, host tree, orchid, PattanunangÂ